FROM CULTURE TO VIRALITY: THE SOCIAL MEDIA EFFECT ON TOURIST DESTINATION IN GREATER JAKARTA AREA - Nathania Wijaya; Amadea Graciella Tjundawan; Deofigrace Waiman; Nadine Christabelle Gadjuli (Center for Scientific Publication, 2025)
Social media platforms such as Instagram or TikTok have shifted how touristsperceive architectural designs of both local and international destinations. Theclickbait-driven content and algorithms used within these platforms expose users tosee similar things repeatedly, which subconsciously change people’s preferences.Builders used this opportunity to recreate “viral” places to repeat the glory of itspredecessor. This research investigates how this phenomenon has shiftedarchitectural typology, particularly within Greater Jakarta. Through a mixed methodapproach that blends architectural theory content analysis from social media posts,surveys, and statistical data, this study aims to investigate the rising trend of“copycat” design to attract a larger audience. Findings reveal a significantcorrelation between viral destinations and architectural development in greaterJakarta. While this trend potentially promotes tourism and potentially economicgrowth, it also sparks debate around the erosion of cultural identity and authenticity.This paper demonstrates that while the so-called “form follows Instagram” approachmight work on a superficial level, it fails to embrace the deeper beauty and locality ofarchitectural design. Furthermore, this paper aims to open a dialogue on the futureof architectural expression in a media-saturated society, where likes and shares shapethe built environment, where copying and pasting are seen as a mere habit.